Establishing Tablet Dissolution Curve Through Determination of Underivatized Alendronate Sodium by Capillary Electrophoresis-UV Detector - Luo, Tian; He, Shujuan; Deng, Yueting; Zhang, Ximin; Dong, Yuming (Current Pharmaceutical Analysis, 2020)
Background: Alendronate sodium is a common clinical osteoporosis drug for postmenopausal women; its determination is very important. However, there is no absorption of chromophores or fluorophores in the molecule, therefore, their direct determination is a challenge. Thus, establishing a common and direct method is very inspiring. Methods: According to the direct determination of alendronate sodium through the formation of a complex between alendronate sodium and divalent copper ion by capillary electrophoresis with ultraviolet detection, the dissolution profile of alendronate sodium tablet was established. The dissolution curves obtained from high-performance liquid chromatography method involving derivatization with 9- fluorenyl methylchloroformate and capillary electrophoresis with ultraviolet detector were found to be highly similar. Underivatized alendronate sodium can be determined by the capillary electrophoresis method. Results: Optimum conditions were as follows: background electrolyte including 25 mM CuSO4 at pH 4.59, 5 s injection time, 18 kV applied voltage, and 240 nm detected wavelength. Method validation indicated good linearity (r2>0.9993), precision of migration time with a relative standard deviation <1.5 % for intra-day and <3.6 % for inter-day, precision of peak areas <2.3 % for intra-day and <5.0 % for inter-day, limits of detection (0.01 μg/mL), limit of quantification (0.04 μg/mL) and recovery (90.6 %- 109.0 %). Conclusion: The proposed capillary electrophoresis method has been proved to be simpler, faster and more convenient to test dissolution profile of alendronate sodium tablet than that of high performance liquid chromatography.
Keywords: capillary electrophoresis